Barriers and enablers to the adoption of halal transportation and halal warehousing services among halal manufacturers in Malaysia - Abdul Hafaz, Ngah (2016)
Increasing in demands for Halal products by Muslims consumers due to their religious obligation has led to the creating of new service known as Halal supply chain. Halal transportation and Halal warehousing are the activities contained in Halal supply chain services. This service were created purely to meet demand from Halal manufacturers who want to protect the credibility of their Halal status. Even more than 2000 companies have been awarded as the Halal manufacturers by Department of Islamic Development (JAKIM), but based on interviewed with the Halal certified service providers, it is only around 15% of the Halal manufacturers were adopting their services. Therefore, by adopting the TOE framework as a theory, this study will try to identify the barriers and the enablers for Halal manufacturers in adopting Halal transportation and warehousing services. By adopting convenience sampling method, a total of 344 respondents were involved in this study. Structured Equation Modeling (SEM) with Partial Least Squares (PLS) version 2.0 has been used to test the relationship between constructs in this study. The study found that perceived benefits, awareness, customer pressures and competitive pressures have significant relationship with the intention to adopt Halal transportation and Halal warehousing services. As expected, cost and complexity were found to be the significant barriers to the adoption of Halal transportation and Halal warehousing services. The study also found that organizational readiness and government support did not have a significant relationship with the intention to adopt Halal transportation and Halal warehousing services. In the early stage, supplier availability was expected to have a positive relationship with the intention to adopt Halal transportation and Halal warehousing services. However, this study found that supplier availability was found to have a negative relationship with the intention to adopt Halal transportation and Halal warehousing services. Top management attitude also did not moderate the positive relationship between perceived benefits and intention to adopt Halal transportation and Halal warehousing services. Beside illustrated the suitability of the PLS statistical analysis, the findings also provided useful information to a better understanding regarding drivers and barriers to the adoption of Halal transportation and Halal warehousing among Halal manufacturers in Malaysia. The findings of this study also could be used by Halal service providers and government agencies to develop a better plan to enhance the adoption rate of Halal transportation and Halal warehousing services among Halal industry players in Malaysia.